Equivalent Equations

Algebra Level 2

If a + b = 1 a + b = 1 , and a 2 b 2 = 3 a^{2} - b^{2} = -3 ; what is the value of ( a b ) (a-b)


The answer is -3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Den Onelle Dujali
Oct 16, 2018

This actually makes use of special products, so we factor a 2 b 2 a^{2} - b^{2} = -3 to ( a + b ) ( a b ) (a + b)(a - b) = -3. From the given information, ( a + b ) = 1 (a + b) = 1 , our equation becomes 1 ( a b ) = 3 1(a - b) = -3 , then we simplify it as ( a b ) = 3 (a - b) = -3 , which is the answer.

Blan Morrison
Oct 16, 2018

Relevant wiki: Difference Of Squares

a 2 b 2 = 3 a^2-b^2=-3 ( a + b ) ( a b ) = 3 \implies(a+b)(a-b)=-3 ( a b ) = 3 \implies (a-b)=-3 β \beta_{\lceil \mid \rceil}


Note that you also could have solved for a a and b b . Here are their values: a + b = 1 a+b=1 a b = 3 a-b=-3 2 a = 2 2a=-2 a = 1 ; b = 2 a=-1;~b=2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...